2019
DOI: 10.1108/bij-12-2018-0449
|View full text |Cite
|
Sign up to set email alerts
|

Environmental training: a systematic review of the state of the art of the theme

Abstract: Purpose The purpose of this paper is to carry out a systematic review of the state of the art of the environmental training theme and to propose a research agenda to shed light on this subject by suggesting new research in the area. Design/methodology/approach This is a systematic review of the state of the art of the environmental training theme. Findings The authors’ main contribution is the proposal of a research agenda with 11 recommendations for future research, such as conducting research in develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Six of the 10 Green HRM literature reviews scoped the concept in entirety while the remaining focused on Green HRM subsets. These subsets, representing standard HRM activities and responsibilities, included green recruitment and/or selection (Adjei‐Bamfo et al 2019), green training (Stefanelli et al 2019) or green employee empowerment (Tariq, Jan and Ahmad 2016).…”
Section: Meta‐analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the 10 Green HRM literature reviews scoped the concept in entirety while the remaining focused on Green HRM subsets. These subsets, representing standard HRM activities and responsibilities, included green recruitment and/or selection (Adjei‐Bamfo et al 2019), green training (Stefanelli et al 2019) or green employee empowerment (Tariq, Jan and Ahmad 2016).…”
Section: Meta‐analysis Resultsmentioning
confidence: 99%
“…Here Yong et al (2019, 2014) reported this to be ‘the most important or useful initiative’ available to organisations when initiating a Green HRM strategy. Moreover, Stefanelli et al’s (2019) review found that 49% of reviewed papers focused on environmental training practices. Pham et al’s (2019) review reported other HRM practices having green focus, including green rewards (49% of reviewed articles), green employee engagement (28%) and green performance management (46%).…”
Section: Meta‐analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To create a classification and coding system, a methodology similar to those used by Stefanelli (2019), Jabbour, Azevedo, Arantes, and Jabbour (2013), and Junior and Godinho Filho (2010) was employed.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The main objective of this paper was to conduct a systematic review of the literature on GSCM in the Latin American context. Studies of this nature are relevant to the development of the proposed themes (Jabbour et al., 2013; Kampen et al., 2012; Stefanelli, Teixeira, Oliveira, Ferreira, & Sehnem, 2019), as they categorize what has already been published on the subject and suggest future research agendas, which may be useful as guiding tools for academics and practitioners who work or are interested in the field.…”
Section: Final Remarksmentioning
confidence: 99%